2008
DOI: 10.1103/physreva.78.052514
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of light shifts at two off-resonant wavelengths in a single trappedBa+ion and the determination of atomic dipole matrix elements

Abstract: We have measured the ratio R of the vector ac-Stark effect (or light shift) in the 6S 1/2 and 5D 3/2 states of a single trapped barium ion to 0.2 % accuracy at two different off-resonant wavelengths. We earlier found R = ∆S/∆D = −11.494(13) at 514.531 nm where ∆S,D are the vector light shifts of the 6S 1/2 and 5D 3/2 m = ±1/2 splittings due to circularly polarized light, and now we report the value at 1111.68 nm, R = +0.4176(8). These observations together yield a value of the 5D||er||4F matrix element, previo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…The expressions (15,16,17) are valid for any isotopes. All dependence on nuclear number A is via weak nuclear charge Q W (see, (2)) while dependence on nuclear radius is negligible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expressions (15,16,17) are valid for any isotopes. All dependence on nuclear number A is via weak nuclear charge Q W (see, (2)) while dependence on nuclear radius is negligible.…”
Section: Resultsmentioning
confidence: 99%
“…Good reviews of the electric dipole transition data in Ba + and Yb + can be found in Ref. [16] and [39].…”
Section: Accuracy Of Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…M1 transitions in Rb, Cs, Ba + , Fr and Fr-like ions are of particular interest due to studies of parity violation [6,7,[13][14][15]. The M1 and E2 transitions in Rb, Cs, Ba + , Yb + , Ra + , Ac 2+ and Th 3+ ions were recently studied by Gossel et al [16], raising the issue of the accuracy of the M1 transition matrix elements.…”
Section: +mentioning
confidence: 99%
“…(Lifetime measurements avoid this calibration challenge by using a well known field, the vacuum.) For atoms with spin-dependent vector light shifts and two long-lived states, rf spectroscopy was used to accurately determine the ratio of two vector light shifts [19,20], which when combined with theory constrained matrix elements [21]. New techniques are needed to improve accuracy, extend the range of measurable matrix elements, and provide benchmarks for theory.…”
mentioning
confidence: 99%